Exact Solution of the Class-E Inverter for Wireless Power Transfer Systems - Bruna C. Nicoletti; Fábio Ecke Bisogno; Lucas S. Mendonça (Eletrônica de Potência, 2025)
This paper introduces the exact solution of the Class-E WPT resonant inverter. Dominantly, the DC-AC inverters for WPT systems are analyzed by assuming a sinusoid waveform for the output variables. However, by allowing waveform light distortions, the magnetic element values can be reduced; which is provided by the proposed method. It is shown that the circuit waveforms are composed of sine, cosine and exponential terms. The obtained solutions are used to design a 500 kHz Class-E WPT resonant inverter which operates with ZVS. The design is experimentally verified and 74 % efficiency with 9.7 W output power is achieved.